2016
DOI: 10.20529/ijme.2016.022
|View full text |Cite
|
Sign up to set email alerts
|

Multiple ethical review in North–South collaborative research: the experience of the Ebola-Tx trial in Guinea

Abstract: The process of double ethical review involves the ethics committees (ECs) in the country(ies) of the research site(s) and of the sponsor. This paper aims to assess the experience of the double ethical review in the Ebola-Tx trial, and to make general recommendations for research conducted during public health emergencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 7 publications
0
37
0
Order By: Relevance
“…The open-label phase 2/3, non-randomized comparative trial was designed to evaluate the feasibility, safety and efficacy of convalescent plasma (CP) against EVD [ 5 , 6 , 23 , 24 , 25 , 26 ]. During the trial (2015), CP was collected through voluntary donations from EVD survivors and subsequently transfused to confirmed EVD patients at the Ebola Treatment Centre led by MSF.…”
Section: Methodsmentioning
confidence: 99%
“…The open-label phase 2/3, non-randomized comparative trial was designed to evaluate the feasibility, safety and efficacy of convalescent plasma (CP) against EVD [ 5 , 6 , 23 , 24 , 25 , 26 ]. During the trial (2015), CP was collected through voluntary donations from EVD survivors and subsequently transfused to confirmed EVD patients at the Ebola Treatment Centre led by MSF.…”
Section: Methodsmentioning
confidence: 99%
“…Although many EC reviews were consistent, some were discordant [34, 62]. Consolidating reviews was explored but proved largely unfeasible.…”
Section: Scientific Data and Safety Monitoring And Ethical Reviewmentioning
confidence: 99%
“…In 2016, a WHO guidance document on ethical issues in outbreaks explicitly recommended that mechanisms must be developed to ensure rapid ethics review without undermining any of the substantive protections that a robust ethics review is designed to provide [7]. However, the guideline does not elaborate on what those mechanisms could be; and it is not clear for how long ethics review bodies may sustain the accelerated review timelines under emergency conditions [8, 2830]. To the best of our knowledge, explicit mechanisms for rapid ethics review have not been put in place yet at the national level, or even piloted in any country.…”
Section: The Five Sessions Of the Who-alerrt Workhopmentioning
confidence: 99%
“…Prior training of ERC members on specific issues relevant for epidemics, and the availability of experts as advisors, was found to be helpful by the Liberian Ethics Committee. The ITM IRB and researchers observed that there is much more to be done to harmonize and streamline the multiple ethical reviews of the same research protocol [30]. Subsequently, participants worked in small groups around case-vignettes (i.e., brief scenarios developed for the purpose of the workshop), in order to discuss the barriers to implementation of the existing normative guidelines, and what would help the N(R)ECs to be better prepared for providing a rapid and robust review of research during an epidemic.…”
Section: The Five Sessions Of the Who-alerrt Workhopmentioning
confidence: 99%